A sensitivity analysis and a comparison of two simulators performance for the process of natural gas sweetening - Gutierrez, Juan Pablo (2016)
Chemical processes simulation is an important instrument for the design, optimization and control of industrial plants. Simulation cases can be accomplished with relatively low costs and the absence of risks for the operators. However, the precision of the results depends on the similarity between the simulation performed and the process considered. In this article, two simulators, Aspen Hysys V8.6 and Aspen Plus V8.6, are employed to simulate the process of natural gas sweetening using diethanolamine (DEA). Additionally, a parametric sensitivity analysis is performed to define the optimal operative range for the process. The required data and the conditions of the operating units are taken from a gas conditioning plant in northern Argentina. Finally, a comparison between the block of obtained results from both simulations is also detailed.